KETERLIBATAN ORANG TUA DALAM KEBERHASILAN ANAK MENJADI SEORANG PENGHAFAL AL-QUR’AN - Fathiyyah, Fathiyyah; Imas Masripah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Parental involvement is a determining factor in a child's success in memorizing the Quran, but the dynamics of this support vary based on family background. This study aims to explore the forms of parental involvement and child characteristics that support successful memorization. Using a descriptive qualitative approach, data were collected through in-depth interviews, observation, and documentation of five families with children who have memorized 1-10 chapters of the Quran. The results of the study indicate that parental involvement manifests in three main forms: (1) psychological support (spiritual motivation), (2) physical facilitation (provision of time and audio media), and (3) pedagogical involvement (regular memorization listening). Interesting findings indicate that educational and economic backgrounds influence mentoring strategies; highly educated parents excel in structured schedule management, while parents with lower-middle incomes excel in the intensity of physical mentoring. The characteristics of children who successfully achieve memorization targets are characterized by strong resilience, self-regulated learning, and adaptive time management. The conclusion of this study confirms that the success of children's memorization is more determined by the quality of interaction and consistency of parental mentoring than simply material facilities. This study recommends the importance of a strategy between parental spiritual motivation and child discipline in maintaining the sustainability of memorization.